A New Global Index of Infrastructure: Construction, Rankings and Applications. (25th July 2015) - Donaubauer, Julian; Meyer, Birgit E.; Nunnenkamp, Peter
Abstract: We construct comprehensive and comparable indices on the most relevant components of economic infrastructure. An unobserved components model is employed to cover the largest possible number of developing and developed countries over the period 1990–2010. We map major findings from the new indices of infrastructure and provide country rankings, which we also compare with subjective assessments of infrastructure in the World Economic Forum's Global Competitiveness Report. Finally, we exemplify possible applications related to trade and foreign aid. By overcoming several data limitations, our new global index can help assess the links between infrastructure and economic development more systematically.